Viability of Immobilized Probiotic Bacteria, Bifidobacterium bifidum, Lactobacillus acidophilus and Lactobacilus casei, in an Emulsion of Corn and Their Survival in Subsequent Treatments - Maligan, Jaya Mahar; Kusnadi, Joni; Murtini, Erni Sofia (Fakultas Teknologi Pertanian Universitas Brawijaya, 2006)
The effectiveness of corn oil emulsion as a protective agent for immobilization of probiotic bacteria cells, B. bifidum, L. acidophilus and L. casei and subsequent treatments, i.e. various conditions of storage and processing, was studied. The immobilized cells were subjected to each of the following: storage conditions at low temperatures 4 ± 1 oC and -10 ± 1 oC, at low pH (pH 1.0 and 2.0), bile salts 2% and processing conditions (25% sucrose solution. 10% brine, and heat treatment up to 80 oC). The statistical approach employed in the experiment was the Post Test Only with control Group Design and a paired sample test was then conducted. The results showed that the viability of the tested probiotic bacteria cells varied with the type of bacteria and conditions of storage processing. The immobilization of probiotics in corn oil emulsion has significant effect on the viability of B. bifidum, L acidophilus and L. casei subjected to temperature of -10 ± 1 oC, at low pH (1.0 and 2.0), heating process and 10% brine. Immobilization process has no significant effect on the viabilities of L. acidophilus and L. casei stored at -10 ± 1 oC, of B. bifidum subjected to bile salts 2% and 25% sucrose solution. Immobilization process in corn oil emulsion was able to retain the probiotics viability as many as 1.12-4.23 log. Therfore, it can be concluded that an emulsion of corn oil is suitable for immobilization media for B. bifidum, L. acidophilus and L. casei protection them during storage at low temperatures, GI tract condition and above mentioned processing conditions. Keywords: Probiotics, viability, immobilization, corn oil emulsion